2021
DOI: 10.1177/2325967121999646
|View full text |Cite
|
Sign up to set email alerts
|

Injury Rates in Major League Baseball During the 2020 COVID-19 Season

Abstract: Background: The 2020 Major League Baseball (MLB) season was drastically altered because of the COVID-19 pandemic. The changes included an extended layoff between March and July as well as a shortened preseason. Purpose/Hypothesis: To determine the incidence and epidemiology of MLB injuries in the abbreviated 2020 season compared with prior seasons. We hypothesized that there was an increase in the overall injury rate in the 2020 season compared with the 2018-2019 seasons and that it equally affected all body r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Studies in soccer and baseball have demonstrated an increase in injury incidence as a result of the COVID-19 pandemic. 18 , 22 …”
mentioning
confidence: 99%
“…Studies in soccer and baseball have demonstrated an increase in injury incidence as a result of the COVID-19 pandemic. 18 , 22 …”
mentioning
confidence: 99%
“…Recently, increased injury rates have been documented following COVID-19 sports suspension in American Major League Baseball [ 21 , 22 ] and the National Football League [ 23 , 24 ]. European reports did not acknowledge the potential complicating factor of the effects of increases in the acute-to-chronic workload ratio (ACWR).…”
Section: Discussionmentioning
confidence: 99%
“…These findings may have been because many teams could no longer practice, a small number of volunteers gathered to practice baseball, and the batting center was often closed due to COVID-19 infection control. Among Major League Baseball players, there were no significant differences in the incidence of injury to the lower extremity between the period before and during the pandemic, which was thought to be the result of isolated exercises and weight training using body-weight muscle strength without any fitness equipment/facilities [20]. In our study, we could not clarify the effect of voluntary exercise; however, we expect voluntary exercise is largely beneficial in terms of promoting physical activities, skill training, and prevention of injuries, especially in the lower extremities, among youth baseball players.…”
Section: Baseball Activitymentioning
confidence: 94%
“…In actuality, the incidence of injuries among Major League Baseball players after the COVID-19 pandemic was almost double of that before the pandemic; the increase in the injury incidence was seen in the upper extremities, spine/core, and other injuries, and not the lower extremities [20]. One of the reasons for the increased injury was the insufficient throwing practice time [20] and throwing in fewer preseason innings [21]. On the other hand, the excessive number of throws [22] and training hours per week [23] were also reported as one of the factors of baseball-related pain in the shoulder and elbow among youth baseball players.…”
Section: Baseball Activitymentioning
confidence: 95%
See 1 more Smart Citation